Harlequin Syndrome Following Resection of Mediastinal Ganglioneuroma - Jeon, Yeong Jeong (Korean J Thorac Cardiovasc Surg, 2017)
Harlequin syndrome is a rare disorder of the sympathetic nervous system characterized by unilateral facial flushing and sweating. Although its etiology is unknown, this syndrome appears to be a dysfunction of the autonomic nervous system. To the best of our knowledge, thus far, very few reports on perioperative Harlequin syndrome after thoracic surgery have been published in the thoracic surgical literature. Here, we present the case of a 6-year-old patient who developed this unusual syndrome following the resection of a posterior mediastinal mass.